IMPLEMENTATION OF THE E-PROCUREMENT SYSTEM IN THE PROCUREMENT PROCESS OF GOODS AND SERVICES AT PT PERTAMINA INTERNATIONAL SHIPPING (JAKARTA) - Sandjaja, Nurlathifah Aurellia Agrippina; Budiatmo, Agung (International Journal Multidisciplinary (IJMI), 2024)
Technological developments have changed the way business is done in Indonesia, pushing companies to adapt quickly. Both digital and non-digital technologies play an important role in managing an increasingly connected and competitive business. In the logistics sector, especially in procurement, technology plays an important role in improving efficiency and transparency. The provision of resources through procurement is a key aspect of logistics management, which requires appropriate regulations and policies to ensure effective fulfillment of needs. This procurement process often involves bidding, both with local and international companies, to select qualified and suitable providers. However, the procurement process certainly has some problems such as the non-processing of a document. One of the state-owned companies that has implemented e-procurement is PT Pertamina International Shipping (PIS). This study aims to identify the application of the e-procurement system and inhibiting factors in the application of the e-procurement system in the process of procuring goods and services at PT Pertamina International Shipping (PIS). The research method used by the author is descriptive qualitative. The data used by the author is obtained through interviews with supporting data related to the problems that occur. The results of this study indicate that the implementation of the e-procurement system at PT Pertamina International Shipping (PIS) has not run optimally because there are still inhibiting factors, namely human resources who have not mastered e-procurement, unstable internet and system errors. Keywords: Implementation System, E-Procurement, Procurement of Goods and Services